Pelatihan Literasi Keuangan Melalui Peramalan Penjualan Camilan Kacang Bawang Pada Rumah Usaha Momprenuner Giwangan Yogyakarta - Sofiati; Oktiva Anggraini; Ika Septi Kurnia Anggraini; Achmad Marzuki (JCSE: Journal of Community Service and Empowerment, 2022)
The market potential for peanut snacks has a high opportunity, thus encouraging mompreuners to always increase production. However, mompreuners face difficulties in determining the optimal amount of production, considering the fluctuating sales results, to maintain the optimal stock of onion bean snacks, the solution is to make sales forecasts. (forecast) sales forecasting. The method applied in this community service is education in the form of training of financial literacy, namely sales forecasting, technology facilitation with Excel software, then the implementation stage is carried out in the form of practice determining sales forecasts. There are three stages in this community service activity, namely (1) Pre-activities, filled with socialization of activities and preparation of educational programs together with mompreuners; (2) Implementation of activities, including financial literacy education (training) in the form of sales forecasts, technology facilitation, and implementation of the practice of making sales forecasts; (3) Post-activity, in the form of monitoring and evaluation of implementation activities. It can be concluded that mompreuners and their employees seem enthusiastic about participating in this community service activity, both during education and financial literacy practices, namely making sales forecasts. Similar programs can be continued with other themes